Measles Distribution Map according to Measles Immunization and Vitamin A Coverage - Vika Gress Vio Dilita; Lucia Yovita Hendrati (Jurnal Berkala Epidemiologi, 2019)
Background: According to the World Health Organization (WHO), Indonesia is one of the ten countries with the most significant number of measles cases in the world. Immunization coverage in Trenggalek Regency has reached the target of prevention of measles in the elimination stage, namely measles immunization coverage> 95%, the incidence of measles persists and increases in the last three years, from 2013 to 2015. Purpose: This study aimed to evaluate the trends between measles immunization status and the provision of vitamin A with the incidence of measles in Trenggalek Regency. Methods: This type of research is an observational study with a cross-sectional study design. The sample population is consist of 14 sub-districts in Trenggalek Regency. Data was taken from the health profile of Trenggalek Regency in 2013, 2014, and 2015. In this study, data processing were analysed by Health Mapper application version 4.3.0.0 with product version 4.03 to determine data descriptively. Results: Distribution of measles incidence with immunization coverage in Trenggalek Regency in 2013, 2014, and 2015 showed that measles incidence tended to increase followed with the decreasing number of measles immunization coverage each year. Ironically, the distribution of measles incidence with vitamin A administration in 2013, 2014, and 2015 showed the incidence of measles had increased because of the inconsistent amount of vitamin A administration. Conclusion: Measles incidence tends to occur in low immunization coverage areas and has decreased from the previous year. Giving vitamin A does not prevent the occurrence of measles, but serves to reduce compilation.